Impairment of coronary flow reserve in orthotopic cardiac transplant recipients with minor coronary occlusive disease. Issue 9 (September 1992) - Mullins, P A; Chauhan, A; Sharples, L; Cary, N R; Large, S R; Wallwork, J; Schofield, P M
Abstract : Objective —Coronary occlusive disease is the major long-term complication after cardiac transplantation. The relation between minor angiographic abnormalities and myocardial perfusion has not been previously assessed in a large number of cardiac transplant patients. Design —Prospective study. Coronary flow reserve was measured with an intracoronary Doppler flow probe in the proximal left anterior descending coronary artery in each patient. A dose of intracoronary papaverine producing maximal vasodilation was then administered. Setting —A regional cardiothoracic centre and a supraregional transplant unit. Patients —Seven patients with chest pain but normal coronary anatomy (controls), and 61 cardiac transplant patients between three months and 10 years after operation (median 4·5 years). Twenty one cardiac transplant patients had angiographic evidence of minor coronary occlusive disease (mean (SD) percentage stenosis diameter 23% (6%)) in a primary or secondary coronary vessel (group 1), with 12 of these in the left anterior descending coronary artery (stenosis diameter (mean (SD) 24% (8%)). The remaining 40 transplant patients had normal coronary angiograms (group 2). Main outcome measure —Coronary flow reserve was defined as the ratio of the peak flow velocity after papaverine to the resting flow velocity. Results —Group 1 patients had a noticeably impaired coronary flow reserve (2·6 (1·1)) compared with control patients (3·9 (0·4), p = 0·05) and, after adjusting for year after operation, compared with group 2 patients (3·8 (1·0), p < 0·001). No other variables were associated with a reduction in coronary flow reserve. Mean resting flow velocity was similar in all three groups (controls, 7·4 (4·6) cm/s; group 1, 7·5 (5·9) cm/s; and group 2, 7·3 (3·9) cm/s). Mean peak flow velocity response to papaverine was reduced in group 1 patients (18·1 (13·5) cm/s) relative to group 2 patients (27·5 (15·4) cm/s, p = 0·05) but not controls (28·4 (15·1) cm/s, p = 0·1). Conclusions —Coronary flow reserve and the peak flow response to the coronary vascular smooth muscle relaxant papaverine are impaired in cardiac transplant patients with minor coronary occlusive disease. This disturbance of cardiac microvascular function may contribute to the late morbidity and mortality seen in cardiac transplant patients with coronary occlusive disease.